Displacement structure approach to Cauchy and Cauchy–Vandermonde matrices: inversion formulas and fast algorithms - Yang, Zheng-Hong; Hu, Yong-Jian (Journal of computational and applied mathematics, 2002)
The confluent Cauchy and Cauchy–Vandermonde matrices are considered, which were studied earlier by various authors in different ways. In this paper, we use another way called displacement structure approach to deal with matrices of this kind. We show that the Cauchy and Cauchy–Vandermonde matrices satisfy some special type of matrix equations. This leads quite naturally to the inversion formulas and fast algorithms for matrices of this kind.